Pemberdayaan Masyarakat Sekitar Masjid Al-Birr Desa Purwodadi Donomulyo Melalui Pengolahan Bahan Pangan Berbasis Ketela Pohon - Maharani, Dian; Kusumastuti, Ari; Zahroh, Fatmawati; Anggraeni, Nurul; Sukron, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The mosque, which has often been used primarily as a place of worship, was also utilized as a gathering and consultation space in this research to discover new breakthroughs in launching a new agricultural processing business. In this study, the community around Masjid Al-Birr in Purwodadi Village, Donomulyo District, was trained to create cassava-based brownies and noodles. The aim of this training was to expand the community's thinking to generate new business ideas while providing innovation in cassava processing. The training took place from May to June 2023. As a result, the community showed enthusiasm and was capable of producing brownies and noodles using cassava as the main ingredient.